Prevalence of bacterial vaginosis in Portuguese pregnant women and vaginal colonization by Gardnerella vaginalis - Daniela Machado; Joana Castro; José Martinez-de-Oliveira; Cristina Nogueira-Silva; Nuno Cerca (PeerJ, 2017)
Background We aimed to determine the prevalence of vaginal colonization by Gardnerella vaginalis and of bacterial vaginosis (BV) in Portuguese pregnant women, and to identify risk factors for BV and G. vaginalis colonization in pregnancy. Methods A cross-sectional study was conducted among pregnant women aged ≥ 18 years who were attending in two public hospitals of the Northwest region of Portugal. Epidemiological data was collected by anonymous questionnaire. BV was diagnosed by Nugent criteria and G. vaginalis presence was identified by polymerase chain reaction. Crude associations between the study variables and BV or G. vaginalis colonization were quantified by odds ratios (ORs) and their 95% confidence intervals (CIs). Results The prevalences of BV and of G. vaginalis colonization among Portuguese pregnant women were 3.88% and 67.48%, respectively. Previous preterm delivery and colonization by G. vaginalis were factors with very high OR, but only statistically significant for a 90% CI. Conversely, higher rates of G. vaginalis colonization were found in women with basic educational level (OR = 2.77, 95% CI [1.33–5.78]), during the second trimester of pregnancy (OR = 6.12, 95% CI [1.80–20.85]) and with BV flora (OR = 8.73, 95% CI [0.50–153.60]). Discussion Despite the lower number of women with BV, prevalence ratios and association with risk factors were similar to recent European studies. However, the percentage of healthy women colonized by G. vaginalis was significantly higher than many previous studies, confirming that G. vaginalis colonization does not always lead to BV development.